Eosinophilia as a treatable trait in three patients with asthma and COPD. Issue 3 (18th January 2018) - Ramsahai, James Michael; Simpson, Jodie; Wark, Peter
Abstract : The combination of asthma and chronic obstructive pulmonary disease (COPD) in an individual can present significant challenges to achieving satisfactory outcomes. More recently, the concepts of precision medicine and treatable traits have arisen as promising tools to improve care for this group. In this series, we present three cases of patients with features of both asthma and COPD in addition to peripheral blood eosinophilia. The novel implementation of personalized management of the individual based on this treatable trait (eosinophilia) resulted in significant benefits. These benefits included improvement in symptoms, lung function, and a marked decline in critical care admissions and exacerbation rates. Abstract : In this series, we present three cases of patients with features of both asthma and chronic obstructive pulmonary disease, in addition to peripheral blood eosinophilia. The novel implementation of the personalized management of the individual based on this treatable trait (eosinophilia) resulted in significant benefits. These benefits included improvement in symptoms, lung function, and a marked decline in critical care admissions and exacerbation rates.